The Environment as a Medium of Original Ideas for Young Researchers in Self-Determined Learning - Munawaroh, Diah Ambarumi; Imrona, Ali; Ahsin, Muhammad Noor; Fauziddin, Moh; Miyono, Noor; Saputra, Nanda; Ridayani (International Journal of Innovative Research and Scientific Studies, 2022)
This article aims to explain young researchers' learning activities at age of 13 to15 years old in formulating original ideas as well as self-determined collaboration and exploration associated with environmental learning activities. This study employs qualitative descriptive research approaches to examine the research learning activities of young researchers in finding self-determined original ideas. This study was carried out in Madrasah Tsanawiyah Negeri (MTsN) Kota Batu, East Java Province, Indonesia. The participants of this study consisted of 22 madrasah students (aged 13-15) who are divided randomly into 12 groups and two research teachers were also involved. The data collection techniques used are observations, interviews, and other documentations. The results of this study indicate that: (1) Students accompanied by teachers are able to think critically about environmental problems in formulating original ideas through teacher's stimulation and habituation to carry out observations both at school and in residence environments that can improve the sensitivity of students in responding to surrounding environmental problems. (2) Students can deliver research ideas to teachers and friends, collaborate, and participate in groups in analyzing, interpreting, designing, implementing as well as reporting activities involved in research projects from the student's point of view. (3) The teacher's habit of stimulating students to obtain original ideas from their surroundings can indirectly lead to an enjoyable research culture for students. The project report is presented as part of this article.